Laryngeal myasthenia gravis following influenza vaccination: a case report and literature review - Feng Wang; Tao Xiang; Lanying He; Jian Wang (Taylor & Francis Group, 2021)
Background Myasthenia gravis (MG) is an autoimmune disease of acquired neuromuscular junction transmission disorder mediated by auto-antibodies. Extranophthalmic muscles are the most susceptible to MG, while the larynx muscle may also be affected. MG can be aggravated by various types of drugs. In the present study, a patient with laryngeal MG who received an influenza vaccination 5 days before onset was treated, which has not been previously reported. Case presentation A 58-year-old Asian woman developed mild dysphagia and severe dysarthria five days after receiving a trivalent inactivated influenza vaccine. The patient's quantitative MG score was 4 (1 for swallowing and 3 for speech), and the patient's neurological symptoms varied. The serum acetylcholine receptor (AChR) antibody titer was 0.67 nmol/L (normal range below 0.2 nmol/L), and other immunological and thyroid function tests were negative. As revealed by chest computed tomography (CT), there was no thymus abnormality. Based on the patient's history, clinical features, and examination results, the patient was diagnosed with laryngeal MG. The patient received pyridostigmine oral administration (60 mg/d) and steroid therapy (Prednisone, oral, 60 mg/d). The patient's symptoms began to improve after 7 days of treatment, and were significantly relieved after 2 weeks. Conclusion Influenza vaccination might cause an unexpected abnormal autoimmune response in MG as a very rare event. Further research is needed to assess the possible causal relationship between the influenza vaccine and neurological complications, also in addition to the safety of the vaccine.